Policing serious crime in China: from "strike hard" to "kill fewer" - Trevaskes, Susan (Routledge studies on China in transition, 2010)
The rise of campaign justice -- The campaign template -- Striking hard in the new millennium -- Cracks in the campaign armour -- The people's war on drugs -- Fighting the collective: the rise of organized crime -- The end of campaign justice?